The Wagnerschule (Vienna 1894-1912): Wagner and the Moderne Architekture - Ettore Sessa (Agathón)
Otto Wagner, between 1894 and 1912, carries out a vertical reform of that principle of the reorganization of the visible which is one of the cornerstones of the Art Nouveau aesthetic revolution. Unlike other Modernist protagonists, the core of pupils of his school (including Hoffmann, Plečnik, Deininger, Schönthal, Hoppe, Fuchs), as well as his assistants (among whom J. M. Olbrich stands out) and the external supporters (applies to all the case of M. Fabiani), although not differentiated on the level of interdisciplinary orientation are distinguished, given the formation, for a peculiar academic footprint of their preparation modern such as to allow them to achieve heterogeneous results on the formal but consistent as regards the method (for the architectural arrangement) and the variables of an even wide range of figural codes; a profile recognizable over time and that has allowed Wagnerschule, despite its being a niche phenomenon, to mark a decisive turning point in the culture of the project of the Contemporary Age.